2019
DOI: 10.3390/su11174736
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Incorporating the Concept of City Sustainability into Sustainability Education Programs

Abstract: This study developed a sustainability education program that incorporated the concept of city sustainability, delivered it to local university students in the Jakarta Metropolitan Area (Jabodetabek), Indonesia, and then evaluated its effectiveness using questionnaire surveys. The educational materials consisted of a case story and scenario analysis report relating to city sustainability. The case story was a fictional narrative describing sustainability issues in Jabodetabek, in which the protagonist is the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…Results of the present contribution revealed that the sample of Spanish pre-service primary teachers hold high levels of sustainability attitudes (in the three dimensions of sustainable development, but above all towards social aspects). Determining the sustainability attitude is important since intentionality is considered a determinant which sets in motion real behavior [77]. Our results agree with a previous work in which the SCQ is used, which it was carried out by Olsson et al [78] with elementary and high school students: gender effects are also reported in some sustainability behavior items and students also assigned the highest mean values to sustainability attitude items.…”
Section: Discussion and Implications For Initial Training Of Primary Teacherssupporting
confidence: 90%
See 2 more Smart Citations
“…Results of the present contribution revealed that the sample of Spanish pre-service primary teachers hold high levels of sustainability attitudes (in the three dimensions of sustainable development, but above all towards social aspects). Determining the sustainability attitude is important since intentionality is considered a determinant which sets in motion real behavior [77]. Our results agree with a previous work in which the SCQ is used, which it was carried out by Olsson et al [78] with elementary and high school students: gender effects are also reported in some sustainability behavior items and students also assigned the highest mean values to sustainability attitude items.…”
Section: Discussion and Implications For Initial Training Of Primary Teacherssupporting
confidence: 90%
“…This gender bias differs from the majority of previous research works about the effect of gender in sustainability consciousness with students of different educational levels, according to which girls hold higher levels of sustainability consciousness [80,84,85]. Nevertheless, some studies also reflected on this unanticipated gender bias, and found that male participants tend to have a more sustainable mindset than female participants [77]. Other studies suggested higher sustainable consciousness among female participants, and this trend has also been observed with samples of pre-service teachers [86,87].…”
Section: Discussion and Implications For Initial Training Of Primary Teachersmentioning
confidence: 58%
See 1 more Smart Citation
“…Educational programs have been regarded as essential elements for sustainable development [28]. The educational subsystem is established in this paper as part of the evaluation, as it is believed that sustainable development is a type of education.…”
Section: Construction and Analysis Of The Index Systemmentioning
confidence: 99%
“…Additionally, there is growing attention toward sustainability education as an important means for addressing environmental issues and accomplishing sustainability. The United Nations Educational, Social, and Cultural Organization (UNESCO) refers to education as a foundation for sustainable development as well as economic growth, peace, and responsible global citizenship [28]. Science and technology are important means to realize sustainable development of agriculture.…”
Section: Construction and Analysis Of The Index Systemmentioning
confidence: 99%